Glutathione-S-Transferase M1, M3, T1 and P1 polymorphisms and susceptibility to non-small-cell lung cancer subtypes and hamartomas - Risch, Angela; Schmezer, Peter; Edler, Lutz; Drings, Peter; Dienemann, Hendrik; Kayser, Klaus; Schulz, Volker; Spiegelhalder, Bertold; Bartsch, Helmut (Pharmacogenetics and genomics, 2001)
Polymorphic glutathione-S-transferase (GST) genes causing variations in enzyme activity may influence individual susceptibility to lung cancer. In this case-control study (consisting of 389 Caucasian lung cancer patients, including 151 adenocarcinomas (ACs) and 172 squamous cell carcinomas (SCCs), and 353 hospital control subjects without malignant disease, genotype frequencies for GSTM1, GSTM3, GSTP1 and GSTT1 were determined by polymerase chain reaction (PCR)/ restriction fragment length polymorphism (RFLP)-based methods. While adjusted odds ratios (ORs) indicated no significantly increased risk for lung cancer overall due to any single GST genotype, the risk alleles for GSTM1, GSTM3 and GSTP1 conferring reduced enzyme activity were present at higher frequency in SCC than in AC patients. This is consistent with a reduced detoxification of carcinogenic polycyclic aromatic hydrocarbons (PAHs) from cigarette smoke that are more important for the development of SCC than for AC. An explorative data analysis also identified statistically significantly increased ORs for the combinations GSTT1 non-null and GSTP1 GG or AG for lung cancer overall (OR 2.23, CI 1.11-4.45), and for SCC (OR 2.69, CI 1.03-6.99). For lung cancer overall, and especially among SCC patients, the GSTT1 null genotype was underrepresented (SCC 11.2%v. control subjects 19%, P = 0.026, OR 0.57, CI 0.30-1.06). Additionally, in 28 patients with hamartomas, the GSTT1 null genotype was also protective (P = 0.013), while GSTP1 variant allele carriers were overrepresented (OR 2.48, CI 1.06-6.51). In conclusion, GST genotypes may act differently, either by detoxifying harmful tobacco carcinogens and/or by eliminating lung cancer chemopreventive agents. The latter role for GSTT1 would explain the observed lower risk of SCC and hamartoma associated with GSTT1 null. Further confirmatory studies are required.
Gesehen am 12.01.2021